2005
DOI: 10.18268/bsgm2005v57n1a5
|View full text |Cite
|
Sign up to set email alerts
|

La falla de Caltepec: raíces expuestas de una frontera tectónica de larga vida entre dos terrenos continentales del sur de México

Abstract: ResumenEn este trabajo se discuten las características geológicas de la falla de Caltepec, una zona de cizalla de larga vida con dirección norte-sur y mecanismo transpresional derecho que separa a los terrenos Zapoteco al oriente y Mixteco al poniente al nivel de sus basamentos metamórfi cos (complejos Oaxaqueño y Acatlán). Los excelentes afl oramientos (área de Caltepec) que exponen completamente el contacto en una anchura variable entre 2 y 6 km revelan una actividad tectonomagmática y metamórfi ca del Pérmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 57 publications
1
34
0
2
Order By: Relevance
“…10b), and the Cuananá plutonic complex in the southern Caltepec Fault zone (ca. 307 Ma; Vega-Carrillo et al, 1998;Elías-Herrera et al, 2005) or their correlatives, that could have provided the Mississippian detrital zircons. Correlative Carboniferous metasedimentary units, such as the Cosoltepec Formation (Talavera-Mendoza et al, 2005), the Tecomate Formation (Kirsch et al, in press), the Salada unit (Keppie et al, 2008a), the Zumpango unit (Ortega-Obregón et al, 2009;RamosArias and Keppie, 2011) and the Coatlaco unit (Grodzicki et al, 2008), each contain a few Mississippian zircons with relatively high Th/U ratios (ca.…”
Section: Provenancementioning
confidence: 99%
“…10b), and the Cuananá plutonic complex in the southern Caltepec Fault zone (ca. 307 Ma; Vega-Carrillo et al, 1998;Elías-Herrera et al, 2005) or their correlatives, that could have provided the Mississippian detrital zircons. Correlative Carboniferous metasedimentary units, such as the Cosoltepec Formation (Talavera-Mendoza et al, 2005), the Tecomate Formation (Kirsch et al, in press), the Salada unit (Keppie et al, 2008a), the Zumpango unit (Ortega-Obregón et al, 2009;RamosArias and Keppie, 2011) and the Coatlaco unit (Grodzicki et al, 2008), each contain a few Mississippian zircons with relatively high Th/U ratios (ca.…”
Section: Provenancementioning
confidence: 99%
“…Immediately, to the west of the study area, locally, around Caltepec and Tlacuilotepec it can be observed beneath Lower Cretaceous red beds, and near Metzontla also below the Matzizi Formation (Elías-Herrera and OrtegaGuti errez, 2002;Elías-Herrera et al, 2005). To the south of the study area, the Metzontla red beds oversteps the Caltepec Fault boundary between the Mixteca and Oaxaca terranes (i.e., Elías-Herrera and Ortega-Guti errez, 2002;Elías-Herrera et al, 2005). Further to the south the Acatlan Complex is covered by Mesozoic and Cenozoic sedimentary rocks (Santamaría-Díaz et al, 2008).…”
Section: Mixteca Terranementioning
confidence: 92%
“…The nearby Acatlan Complex comprises schists (mica schist, amphibolites, quartzfeldespathic schist, greenschist), quartzite, and some bodies of serpentine (Elías-Herrera and Ortega-Guti errez, 2002;Elías-Herrera et al, 2005). The mineral associations in these rocks indicate high-and low-grade metamorphism.…”
Section: Mixteca Terranementioning
confidence: 99%
“…Keppie et al, 2001Keppie et al, , 2003Solari et al, 2003;Gillis et al, 2005); estas edades también se han reportado en rocas del Complejo Acatlán y en algunos granitoides que lo cortan (cf. Elías-Herrera et al, 2005;Talavera-Mendoza et al, 2005;Vega-Granillo et al, 2007;Nance et al, 2007;Keppie et al, 2007;Ortega-Obregón et al, 2009) localizados al poniente y suroeste del área de estudio, así como en las areniscas de la Formación Todo Santos (Pérez-Gutiérrez et al, 2009) (Figuras 9 y 10). …”
Section: Fuente De Los Circones Detríticosunclassified
“…fuentes de procedencia. Estos sedimentos se generaron muy probablemente en las regiones de Teotitlán y Oaxaca, localizadas hacia el sureste del área (Delgado-Argote et al, 1992;Alaniz-Álvarez et al, 1996;Ángeles-Moreno, 2006;Ángeles-Moreno et al, 2012); y en menor medida en el poniente (Elías-Herrera et al, 2005;Talavera-Mendoza et al, 2005;Vega-Granillo et al, 2007;Mendoza-Rosales, 2010). El hecho de que las rocas calcáreas del AptianoAlbiano cubran discordantemente a las rocas del Complejo Oaxaqueño al sur del área de estudio (Wilson y Clabaugh, 1970), así como a las rocas paleozoicas y jurásicas, permite suponer que estas se encontraban expuestas a la erosión durante el depósito de la Formación Chivillas, como se aprecia en los atributos sedimentarios de la columna estratigráfica, en la cual podemos reconocer una estratigrafía invertida con base en los clastos presentes en las debritas.…”
Section: Bosquejo Paleográficounclassified